Mental illness, journalism investigation and the law in Australia and New Zealand - Mark Pearson (Asia Pacific Network, 2011)
Mental illness, its terminologies, definitions, voluntary and compulsory treatment regimes, and its interface with the criminal justice system are defined and regulated remarkably differently across the 10 Australian and New Zealand jurisdictions. This presents a legislative and policy nightmare for the investigative journalist attempting to explain the workings of the mental health system or follow a case, particularly if the individual’s life has taken them across state or national borders. This article considers the extent to which legal restrictions on identification and reportage of mental health cases in Australia and New Zealand inhibit the pursuit of ‘bloodhound journalism’—the persistent pursuit of a societal problem and those responsible for it. It recommends the development of resources assisting journalists to navigate the various mental health regulatory regimes. It also calls for the opening of courts and tribunals to greater scrutiny so that the public can be better educated about the people affected by mental illness and the processes involved in dealing with them, and better informed about the decisions that deprive their fellow citizens of their liberty.